2022
DOI: 10.3389/fgene.2022.962028
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and immunological role of cuproptosis-related protein FDX1 in pan-cancer

Abstract: Background: Cancer is the second cause of death worldwide. Copperoptosis is a new mode of regulated cell death and is strongly associated with metabolic pathways. FDX1 is a key gene that promotes copperoptosis, and its impact on tumor pathogenesis and tumor immune response is indistinct and needs further exploration.Methods: Data was mined from the Cancer Genome Atlas database, the Broad Institute Cancer Cell Line Encyclopedia database, and the International Cancer Genome Consortium. Survival analyses included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In addition, lower expression of the FDX1 gene was reported to be closely associated with more advanced tumor-node-metastasis stages [161]. Furthermore, lower expression of FDX1 in various cancer types has been correlated with shorter survival times [13,162,163]. Despite these findings, cuproptotic events have not been well documented in diverse cancers.…”
Section: Cuproptosis In Proliferation and Metastasismentioning
confidence: 99%
“…In addition, lower expression of the FDX1 gene was reported to be closely associated with more advanced tumor-node-metastasis stages [161]. Furthermore, lower expression of FDX1 in various cancer types has been correlated with shorter survival times [13,162,163]. Despite these findings, cuproptotic events have not been well documented in diverse cancers.…”
Section: Cuproptosis In Proliferation and Metastasismentioning
confidence: 99%
“…DLD, a positive regulator of cuproptosis, enhances copper-dependent cell death, which may provide new ideas for the therapeutic action of certain cancer-targeted drugs ( Xiao et al, 2022 ). Previous studies have revealed that DLD is associated with several neurodegenerative diseases ( Yan et al, 2008 ), and DLD deficiency may lead to several fatal metabolic diseases ( Ambrus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The properties of tumors include biological behaviors acquired during their development, such as evasion of growth inhibitors, resistance to cell death, and achievement of replicative immortality ( Hanahan and Weinberg, 2011 ). Tumor occurrence and development are complex multifactorial processes driven by genetic variation: carcinogenesis is promoted and developed, and carcinogenic components change and induce proliferation ( Xiao et al, 2022 ). Thus, the development of more effective approaches for the early detection and treatment of tumors will help reduce cancer mortality ( Bray et al, 2018 ; Cheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we identi ed 5 CRGs (FDX1, LIAS, LIPT1, PDHA1, DLD) to predict the prognosis for patients with THCA, which was con rmed in vitro. FDX1, a core molecular of cuproptosis reducing Cu 2+ to Cu + , was downregulated in most kinds of cancers (43). Lipoic acid synthetase (LIAS), a key enzyme synthesizing lipoate, has been proven to be involved in several metabolic diseases, including cancer (44).…”
Section: Discussionmentioning
confidence: 99%